A Case Study on Challenges of Students' Willingness to Orally Respond in English during Class Sessions in Sabah - Bernadette Tobi; Mohammad Aqmal Hafidz Musa; Nor Dawirah Rahman; Sabariah Abd Rahim (Global Academic Excellence, 2022)
Students’ willingness to respond in class is an important factor to ensure language usage and language acquisition. Literature reviews reveal that learners' levels of anxiety and self-confidence are predictors of students’ willingness to communicate in class. However, there has been a lack of studies conducted in the local context regarding anxiety as a predictor of willingness to respond in English. This study looked into students’ anxiety levels while communicating in English during Occupational Purpose class and the reasons for not being willing to respond in the online class orally. The class consisted of students from Malaysia and China studying in a local Malaysian university. During class, the instructor had to call out names to get students to answer questions asked. Classes were entirely conducted online and the assessments cover both written and oral aspects. Horwitz’s Foreign Language Classroom Anxiety Scale (FLCAS) was adapted and Baharuddin’s three levels of anxiety mean measurement was used in this study. The FLCAS scale included 33 items of a five-point Likert scale which in this study was reversed with 1 “Strongly disagree” to 5 “Strongly agree” to measure the level of anxiety. The data obtained were analysed using descriptive analysis to include percentages and mean. The finding indicates that level of anxiety is not a predictor of WTC.